2001
DOI: 10.1002/jcb.1200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteoclastogenesis and RANK expression by TGF‐β1

Abstract: Transforming growth factor-beta (TGF-beta) has been shown to both inhibit and to stimulate bone resorption and osteoclastogenesis. This may be due, in part, to differential effects on bone marrow stromal cells that support osteoclastogenesis vs. direct effects on osteoclastic precursor cells. In the present study, we used the murine monocytic cell line, RAW 264.7, to define direct effects of TGF-beta on pre-osteoclastic cells. In the presence of macrophage-colony stimulating factor (M-CSF) (20 ng/ml) and recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 15 publications
4
74
0
Order By: Relevance
“…TGFβ was shown to enhance osteoclast differentiation, also attracting monocytes and fibroblasts (Bonewald & Mundy, 1990;Filvaroff et al, 1999;Hock, Canalis & Centrella, 1990;Karst et al, 2004;Koseki et al, 2002;Kubota et al, 1990;Massey et al, 2001;Mundy, 1991;Pilkington, Sims & Dixon, 2001;Sells Galvin et al, 1999;Yan et al, 2001). IGF-I and II stimulate cell proliferation and differentiation and may have a role in orthodontic tooth movement (Canalis et al, 1989;Mochizuki et al, 1992;Raisz et al, 1993a;Spencer et al, 1991;Thaller et al, 1993).…”
Section: Biological Factors In Rate Of Tooth Movement and Errmentioning
confidence: 99%
“…TGFβ was shown to enhance osteoclast differentiation, also attracting monocytes and fibroblasts (Bonewald & Mundy, 1990;Filvaroff et al, 1999;Hock, Canalis & Centrella, 1990;Karst et al, 2004;Koseki et al, 2002;Kubota et al, 1990;Massey et al, 2001;Mundy, 1991;Pilkington, Sims & Dixon, 2001;Sells Galvin et al, 1999;Yan et al, 2001). IGF-I and II stimulate cell proliferation and differentiation and may have a role in orthodontic tooth movement (Canalis et al, 1989;Mochizuki et al, 1992;Raisz et al, 1993a;Spencer et al, 1991;Thaller et al, 1993).…”
Section: Biological Factors In Rate Of Tooth Movement and Errmentioning
confidence: 99%
“…It seems that regulation of osteoclastogenesis and osteoclast activity in scorbutic rats may also be influenced by some unidentified factors in addition to the osteoblast-mediated RANK-RANKL interactions (Suda et al, 1999). In fact, Yan et al (2001) reported direct stimulation of osteoclastic differentiation by TGF-␤1, accompanied by increased RANK mRNA and protein.…”
Section: Osteoblasts and Osteoclastsmentioning
confidence: 99%
“…It could therefore be inferred that osteoclastogenesis regulation in PR animals may be affected by other factors besides osteoblast-osteoclast interaction mediated by RANK-RANKL (receptor activator of nuclear factor-Kappa B-RANK ligand) 15 and TGFb 1 (transforming growth factor beta 1) associated with an increase in RANK RNA messenger and protein. 16 On the other hand, it is well documented that severe protein undernutrition affects visceral proteins, particularly albumin and carrier proteins. Protein malnutrition also produces severe hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%